Goals and Objectives of Physical Education of School Children - Shomuratov Askar Abdullaevich (Research Parks Publishing LLC, 2021)
In accordance with the decision of the President and the Cabinet of Ministers of the Republic of Uzbekistan on measures for further development of physical culture and sports in the Republic of Uzbekistan, special tests